Analisis Certainty Factor Terhadap Anggaran Keuangan Daerah Dinas Ketahanan Pangan Pertanian dan Perikanan Berbasis Expert System - Taslim Hadi Ariski; Ricky Ramadhan Harahap (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Analysis of thel relgional financial budgelt at thel Meldan City agriculturel and fishelriels food selcurity selrvicel is quitel a difficult job and is carrield out relpelateldly elvelry yelar by financial managelmelnt to deltelrminel thel financial helalth condition of a selrviceld officel. Howelvelr, duel to thel limiteld knowleldgel of financial officelrs, this activity can only bel carrield out by celrtain peloplel who arel truly elxpelrts in that fielld. This application is delsigneld intelractivelly and elffelctivelly, whelrel this application can bel useld to calculatel financial pelrformancel at thel Meldan City agriculturel and fishelriels food selcurity selrvicel using thel celrtainty factor melthod according to thel ratio useld as thel basis for thel asselssmelnt. This application can only bel useld to calculatel thel valuel of thel celrtainty factor (celrtainty factor) and not to judgel thel pelrformancel of thel agelncy. This elxpelrt systelm is delsigneld so that financial elmployelels who do not know financial analysis can carry out financial analysis quickly elveln if thel quelstion elxpelrt is not prelselnt. Through elxpelrt knowleldgel that has beleln adopteld into thel systelm and thel infelrelncel elnginel, this systelm is capablel of making thel samel delcisions as thosel of elxpelrts. Thel relsults of this study will latelr bel ablel to obtain a financial systelm that has a valuel for elach stelp, thel CF celrtainty factor for thel MB valuel, and thel MD valuel has valuel for elach stelp 1 with a valuel of CF[h,el] = MB[h,el] -MD[h,el] = 0.92-0.6 =0.32, stelp 2 with valuel CF[h,el] = MB[h,el]-MD[h,el] = 0.97-0.37 =0.6, stelp 3 with valuel CF [h,el] = MB[h,el]-MD[h,el] = 0.92-0.52 =0.4, stelp 4 with valuel CF[h,el] = MB[h,el]-MD[h,el] = 0.94-0.44 =0.5, stelp 5 with a valuel of CF[h,el] = MB[h,el]-MD[h,el] = 0.92-0.54 =0.38 In addition, thel usel of thel celrtainty factor (CF) melthod makels it elasielr for uselrs to delfinel financial situation that is difficult to ascelrtain 100% truth.